GP triage to paediatric rheumatology clinic following the introduction of choice and book. (4th April 2011) - Leone, V; Foster, H; Friswell, M
Abstract : Aims: General Practitioners (GPs) using 'Choose and Book' can select a new patient slot in either a 'non-inflammatory clinic' or in a 'fast track' clinic for children with suspected inflammatory joint disease. The referrer is provided with online access to Service Selection information to help identify the most suitable clinic according to the patients' presentation. To audit sensitivity, specificity and predictive value of GPs' triage into inflammatory and non-inflammatory clinics compared with initial clinical diagnosis by consultant paediatric rheumatologist. To review if outcomes of patients with inflammatory conditions are influenced by GP's triage process. Methods: A retrospective case notes audit of 58 consecutive patients referred to Paediatric Rheumatology via Choice and Book from April 2007 to August 2008. The audit was registered with the Trust R and D department. Results: 52/58 patients records were available for the analysis including 39 non-inflammatory conditions, 11 inflammatory conditions (seven juvenile idiopathic arthritis (JIA) and four transient inflammatory conditions) and two unclear cases. Referring GPs did not indicate a diagnosis in 28/52 cases; where a diagnosis was suggested, GP's triage into inflammatory and non-inflammatory conditions had a sensitivity of 83%, specificity of 78% with a positive predictive value (PPV) of 56%. The GP's triage into the correct clinical service had a sensitivity of 73%, specificity of 72% and PPV value of 42%; 3/11 children with JIA were booked into a non-inflammatory clinic; 11/39 children with a non inflammatory condition were fast-tracked into an inflammatory clinic. There were seven patients with JIA. The mean time from the onset of symptoms to the first treatment (either joint injection or DMARD) was 714 days (213–1747 days); mean time from referral to clinic appointment was 5.64 weeks. The mean time from the first clinic appointment to the first treatment was 25 days (0–42 days). Conclusions: GPs did not suggest a provisional diagnosis in >50% cases and triage into the correct clinical service was sub-optimal. Patients with JIA had significant delay between the onset of symptoms and initiation of treatment. There is need to improve the triage process and facilitate early recognition of JIA to enable more effective use of the Choose and Book system and better outcomes for children.